S-phase kinase-associated protein 2 promotes cell growth and motility in osteosarcoma cells. Issue 16 (18th August 2017) - Ding, Lu; Li, Rong; Sun, Rongxin; Zhou, Yang; Zhou, Yubo; Han, Xiaoping; Cui, Yong; Wang, Wu; Lv, Qing; Bai, Jingping
ABSTRACT: Skp2 (S-phase kinase-associated protein 2) plays an oncogenic role in a variety of human cancers. However, the function of Skp2 in osteosarcoma (OS) is elusive. Therefore, in the current study, we explore whether Skp2 exerts its oncogenic function in OS. The cell growth, apoptosis, invasion and cell cycle were measured in OS cells after Skp2 overexpression. We found that overexpression of Skp2 enhanced cell growth, and inhibited cell apoptosis in OS cells. Moreover, we observed that upregulation of Skp2 accelerated cell cycle progression in OS cells. Furthermore, the ability of migration and invasion was enhanced in Skp2 overexpressing OS cells. Mechanically, our Western blotting data suggested that Skp2 decreased the expression of E-cadherin, Foxo1, p21, and p57, but increased MMP-9 in OS cells. In conclusion, our study demonstrated that Skp2 exhibited an oncogenic function in OS cells, suggesting that inhibition of Skp2 may be a novel approach for the treatment of OS.